Geology of pluvial Lake Chewaucan, Lake County, Oregon - Allison, Ira S. (Ira Shimmin) 1895-1990 (Oregon State monographs. Studies in geology, 1982)
Pluvial Lake Chewaucan was a late Pleistocene lake, as much as 375 feet deep, covering 480 square miles in the northwestern part of the Great Basin in southern Oregon. The lake basin, now occupied by Summer Lake, Upper and Lower Chewaucan Marshes, and Lake Abert, was formed by down-dropped fault blocks bounded by imposing fault scarps, notably Winter Ridge and Abert Rim. Several large landslides occurred along the east side of Winter Ridge. Lake Chewaucan shore features include wave-cut cliffs and caves, beaches, terraces, bay bars, spits (as at The Narrows), and a huge alluvial fan built by Chewaucan River at Paisley. Later, at lower lake stages, part of the fan deposit of sand and gravel was distributed across four-mile-wide Paisley Flat, which subsequently became a divide between Winter Lake in the Summer Lake basin and ZX Lake (new name) in the Chewaucan Marshes-Lake Abert part of the Lake Chewaucan basin. Overflow from ZX Lake later cut a shallow channel across the divide enroute to Winter Lake. The bottom sediments of Lake Chewaucan are exposed mainly in the bluffs of Ana River, the main source of Summer Lake water. The stratigraphic section there is about 54 feet thick and composed mainly of silt, with numerous seams of sand, oolites, occasional pebbles, and many layers of volcanic ash, especially near the top. Fossils found in the area include 1) mammals and birds obtained from man-occupied caves near Paisley, 2) ostracods, diatoms, and small mollusks in the Ana River section, 3) similar tiny snail shells in a gravel pit north of the Ana Springs Reservoir, and 4) additional shells from the 4425-foot level near Ten Mile Butte east of Summer Lake. The snail shells have radiocarbon ages of >25,900, 22,000, and 17,500 years - all within the span of the Tioga-Pinedale glacial stage of the Sierra Nevada and the Rocky Mountains. The top 4520-foot shoreline, the 4485-foot beach and Paisley Caves, and the bulk of the Paisley fan may possibly be Tahoe in age, but the wave erosion of the Paisley fan, development of Paisley Flat, overflow from ZX Lake, and later formation of ZX Red House beach are assigned to Tioga-Pinedale time. The history of Lake Chewaucan is thought to be analogous to those of Lake Bonneville, Lake Lahontan, and Searles Lake, and correlative with climatic changes recorded in marine deposits. The post-Lake Chewaucan history of the basin includes Anathermal, Altithermal, and Medithermal climatic changes, as shown by a pollen profile in Upper Chewaucan Marsh. Mount Mazama pumice sand fell in the area about 6,600-6,700 years ago. Desiccation and wind work were strong in Altithermal time. In the Neopluvial (new term), corresponding to Neoglaciation in the mountains (perhaps 4,000-2,000 years ago), new lakes many tens of feet deep developed in the Summer Lake and Chewaucan Marshes-Lake Abert basins. Later, Summer Lake and Lake Abert were reduced to the very shallow, alkaline bodies of water of the present day.